2016
DOI: 10.7150/thno.16183
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Barriers of Light Penetration: Strategies, Perspectives and Possibilities for Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a photochemistry based treatment modality that involves the generation of cytotoxic species through the interactions of a photosensitizer molecule with light irradiation of an appropriate wavelength. PDT is an approved therapeutic modality for several cancers globally and in several cases has proved to be effective where traditional treatments have failed. The key parameters that determine PDT efficacy are 1. the photosensitizer (nature of the molecules, selectivity, and macroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
249
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(254 citation statements)
references
References 177 publications
(191 reference statements)
0
249
0
5
Order By: Relevance
“…The separation of tumors into small and large groups illuminates the distinct size‐dependent therapeutic efficacy of PDT in this model, which can be attributed to a number of causes. Light scattering properties of tissue limit the effective depth penetration of 690 nm light to several millimeters . Spherical tumors with a volume of 65 mm 3 (the largest in this study at the time of PDT treatment) have a diameter of 5 mm, suggesting that the entire tumor may not receive the full light dose.…”
Section: Discussionmentioning
confidence: 88%
“…The separation of tumors into small and large groups illuminates the distinct size‐dependent therapeutic efficacy of PDT in this model, which can be attributed to a number of causes. Light scattering properties of tissue limit the effective depth penetration of 690 nm light to several millimeters . Spherical tumors with a volume of 65 mm 3 (the largest in this study at the time of PDT treatment) have a diameter of 5 mm, suggesting that the entire tumor may not receive the full light dose.…”
Section: Discussionmentioning
confidence: 88%
“…To this end, we specifically investigated and reported the efficacy of IR700-YY146 PIT in melanomas. [43] Delivering light to large or disseminated tumors has been largely limited by attenuation in potency as the light penetrates into deep tissues, resulting in reduced efficacy of PDT in tumor tissues. Moreover, we found that production of surplus ROS (including singlet oxygen), reduced glucose metabolism and suppression of CD146 expression synergistically contribute to the superior therapeutic effect of IR700-YY146 PIT in small melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…The strong antitumor effect of IR700-YY146 PIT herein raises the possibility that IR700-YY146 PIT is a promising therapeutic option for early-stage cutaneous melanomas, provided that the tumor is CD146-positive. [43] However, future studies are needed to shed light on the impact of repeated IR700-YY146 PIT and dosage of IR700-YY146 (or laser) on the therapeutic outcome in advanced large melanomas. Overwhelming ROS production may play a key role in mediating the treatment outcome, since Fujimoto et al previously reported that ROS scavengers obviated the therapeutic efficacy of IR700-mAb conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…The dye has a strong absorption peak close to 700 nm allowing light to penetrate deep into the tissue [70,71]. Moreover, IR700 does not develop off-target effects since they cannot be taken up by cells and cannot exert cytotoxicity even after illumination [72,73]. …”
Section: Photoimmunotherapymentioning
confidence: 99%